Fox News – Breaking News Updates

latest news and breaking news today

If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0? -4
-2
2
4

source : e-eduanswers.com

If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0? -4
-2
2
4

(f + g)(x) = 0 if value of x= -2

Step-by-step explanation:

f(x)=x^2-2x and g(x)=6x+4 then find

(f+g)(x)=0

We know that (f+g)(x)=0 is equal to f(x)+g(x)=0

Solving:

f(x)+g(x)=0

x^2-2x+(6x+4)=0

x^2-2x+6x+4=0

x^2+4x+4=0

Now factorizing to find value of x

x^2+2x+2x+4=0

x(x+2)+2(x+2)=0

(x+2)(x+2)=0

x+2=0 and x+2=0

x=-2 and x=-2

So, (f + g)(x) = 0 if value of x= -2

Keywords: Composition of functions

Learn more about Composition of functions at:

#learnwithBrainly

Operations on Functions | Purplemath

Operations on Functions | Purplemath – Given f (x) = 3x 2 – x + 4, find the simplified form of the following expression, and evaluate at h = 0: This isn't really a functions-operations question, but something like this often arises in the functions-operations context.Simple and best practice solution for g(x)=2x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework. If it's not what You are looking for type in the equation solver your own equation and let us solve it.Solution for F(x)=x2+6x+5 equation: (F)=F2+6F+5 We move all terms to the left: (F)-(F2+6F+5)=0 We add all the numbers together, and all the variables-(+F^2+6F+5)+F=0 We get rid of parentheses-F^2-6F+F-5=0 We add all the numbers together, and all the variables-1F^2-5F-5=0 a = -1; b = -5; c = -5; Δ = b 2-4ac Δ = -5 2-4·(-1)·(-5) Δ = 5 The delta value is higher than zero, so the equation has

g(x)=2x-6 – solution – Free equations calculator – solve linear, quadratic, polynomial, radical, exponential and logarithmic equations with all the steps. Type in any equation to get the solution, steps and graphHow can the graph of g(x)=1/3x 3 – 5 be obtained from the graph of f(x)=x 3? A. Shrink vertically and shift down 5 units. B. Stretch vertically and shift up 5 units.4.3 Solve g-x 2 +2x-1 = 0 In this type of equations, having more than one variable (unknown), you have to specify for which variable you want the equation solved. We shall not handle this type of equations at this time.

g(x)=2x-6 - solution

F(x)=x2+6x+5 – Get Easy Solution – Simple Interest Compound Interest Present Value Future Value. Conversions. Decimal to Fraction Fraction to Decimal Hexadecimal Scientific Notation Distance Weight Time. Equation Calculator x^2-6x-12=0. Equations. Basic (Linear) x^{2}-6x-12=0. en. Related Symbolab blog posts. High School Math Solutions – Quadratic Equations Calculator, Part 1.If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0? – 7603422 Answer: -2. Step-by-step explanation: The given functions : Then the combine function of the above function is given by :-In mathematics, function composition is an operation that takes two functions f and g and produces a function h such that h(x) = g(f(x)).In this operation, the function g is applied to the result of applying the function f to x.That is, the functions f : X → Y and g : Y → Z are composed to yield a function that maps x in X to g(f(x)) in Z.. Intuitively, if z is a function of y, and y is a

Untitled
JEE Main 2020 Sample Mock Paper-4 – MathonGo
1. Functions
1. Functions
SKILLS AND CONCEPTS
Bargain Dental Supply – Discounted Dental Supplies
Revision – Additional Mathematics F4.1 - Functions 1. Set A = {4, 8, 12} Is  Related To Set B = {2, 3, 4 ,5} By The Relation